Linguistic Features Of Advertising Slogans Of Soft Drinks In English And Vietnamese - Đặng Trần Hoài Dương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis mainly aims at finding the similarities and differences of advertising slogans of soft drinks in English and Vietnamese in terms of syntax and semantics and stylistics. Through an investigation onto linguistic features of advertising slogans of soft drinks in English and Vietnamese, the author hope to bring about certain benefits to the readers themselves. The data of the study was collected from English, Vietnamese newspapers, magazines, from television, radio, posters, signboards or websites of companies. The data were described and contrastively analyzed in terms of syntax, semantics and stylistic aspects under qualitative and quantitative approaches to yield more precise points in advertising slogans of soft drinks in terms of syntax, semantics and stylistic. The findings showed that both English and Vietnamese use a lot of structures as means of adverting such as noun phrase, adjective phrase and verb phrase, imperative, ellipsis... They also consist of semantic features such as hyponym, synonym and antonym. Besides, stylistic devices used in English and Vietnamese advertising slogans of soft drinks have high artistic effects in the way of expressing, drawing attention to products, making a strong impression on customers in order to arouse their interest of buying the products. In addition, the thesis tries to find out some commonly used syntactic and semantic features as well as stylistic devices in advertising slogans of soft drinks in English and Vietnamese. With an eye to partly contributing to better teaching and learning English as a foreign language, specifically to better the awareness of learners in translating and writing an advertisement, some suggested ideas are also included.